Prospects for rice exports in Bangladesh - Goletti, Francesco; Jahangir, A. S. M.; Zohir, Sajjad (International Food Policy Research Institute, 2000)
What is Bangladesh's potential for self-sufficiency in rice production? There have been both optimistic and pessimistic answers to that question. Observers expressed optimism in the early 1990s, when rice surpluses were publicized (World Bank 1992). Trends in production and prices supported that attitude: even with excessive flooding in 1988, farmers were able to cope, and aggregate rice production did not decline as anticipated. In subsequent years the country had good harvests, and increased adoption of modern rice varieties and expansion of boro plantings raised total rice productivity (see Chapter 2). With an enormous stock buildup in the public storage system, the government soon found it unfeasible to continue its procurement program. Even with declining imports, the real price of rice continued to drop, reaching a new low when, compared with the previous year, aman paddy prices declined by 25.4 percent in December 1992/January 1993 and boro prices declined by 33.6 percent in May/June 1993.